On the intertextuality of Paria [The Pariah] by Chęciński and Moniuszko - Borkowska-Rychlewska, Alina (Interdisciplinary Studies in Musicology, 2023)
Stanisław Moniuszko’s opera about Pariah which was based on Casimire Delavigne’s tragedy from 1821, expressed the composer’s dream of creating a cosmopolitan and ‘European’ work with universal message. Usually, the researchers review this aspect from the perspective of music and culture studies, e.g. searching for a relationship between The Pariahand Moniuszko’s contemporary opera music or focusing on the 19th-century views on the effect of class inequalities and social exclusion. However, equally interesting are the diverse and complex relationships of The Pariah’s libretto with 19th-century literature, rarely taken up and investigated in the research into Moniuszko’s legacy. Jan Chęciński’s text, apart from the obvious dependence of the story and playwriting on the French playwright’s tragedy, has its theme and linguistic style deeply rooted in Polish and European 19th-century literary tradition created, among others, by Mickiewicz, Malczewski, Byron and Scribe. Given Moniuszko’s desired cosmopolitanism and universality of The Pariah, this is an issue which is undoubtedly very important.